Writing RFPs for Assessment Programs - Pamela E. Aschbacher (Practical Assessment, Research, and Evaluation, 1989)
Accessed 26,755 times on https://pareonline.net from November 13, 1999 to December 31, 2019. For downloads from January 1, 2020 forward, please click on the PlumX Metrics link to the right.
Keywords: Administrator Role; *Bids; Educational Assessment; Evaluation Methods; Financial Support; *Program Proposals; *Proposal Writing; Public Agencies; *Research Proposals; School Districts; State Agencies; *Technical Writing